2021
DOI: 10.1002/ecs2.3360
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid stable isotopes add clarity, but also complexity, to tracing energy pathways in aquatic food webs

Abstract: Tracing the flow of dietary energy sources, especially in systems with a high degree of omnivory, is an ongoing challenge in ecology. In aquatic systems, one of the persistent challenges is in differentiating between autochthonous and allochthonous energy sources to top consumers. Bulk carbon stable isotope values of aquatic and terrestrial prey often overlap, making it difficult to delineate dietary energy pathways in food webs with high allochthonous prey subsidies, such as in many northern temperate waterbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Including isotopic fractionation terms into the model would certainly be more accurate, but to our knowledge only few data are available for higher marine organisms (see above). Furthermore, experimental work has shown that δ 13 C FA values of PUFAs can also be modified via fractionation when being incorporated into lipids in various tissues (Gladyshev et al 2016), or by metabolic processes (Chiapella et al 2021). Although it is difficult to map the individual steps of isotopic fractionation into total metabolism, we recognize a need for increased attention towards the kinetics of metabolic processes.…”
Section: Issuementioning
confidence: 99%
“…Including isotopic fractionation terms into the model would certainly be more accurate, but to our knowledge only few data are available for higher marine organisms (see above). Furthermore, experimental work has shown that δ 13 C FA values of PUFAs can also be modified via fractionation when being incorporated into lipids in various tissues (Gladyshev et al 2016), or by metabolic processes (Chiapella et al 2021). Although it is difficult to map the individual steps of isotopic fractionation into total metabolism, we recognize a need for increased attention towards the kinetics of metabolic processes.…”
Section: Issuementioning
confidence: 99%
“…Compound‐specific stable isotope analysis (CSIA) of individual AAs or fatty acids (FAs) continues to grow as a robust proxy for tracing energy sources and estimating consumer TL. For example, FA δ 2 H and δ 13 C values are promising tracers for food web studies (Anparasan & Hobson, 2021; Budge et al, 2011; Burian et al, 2020; Chiapella et al, 2021; Wang et al, 2015), especially those in which consumers rely on both terrestrial and aquatic resources. Aquatic algae and terrestrial plants typically have distinct FA profiles, with algae containing higher concentrations of polyunsaturated fatty acids (PUFAs; Gladyshev et al, 2013; Hixson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We quantified each δ 13 C PUFA value to follow dietary PUFA sources for Daphnia by calculating the difference in δ 13 C of each FA between the consumer ( δ 13 C C ) and its respective diet sources ( δ 13 C D ), i.e. Δ 13 C FA , following Chiapella et al ( 2021 ): Δ 13 C FA = δ 13 C C − δ 13 C D . In a similar way, we calculated Δ 13 C FA differences within Daphnia between LIN ➔ ARA, ALA ➔ SDA, ALA ➔ EPA, and SDA ➔ EPA conversion pathways.…”
Section: Methodsmentioning
confidence: 99%